A Scoping Review of COVID-19 in the Context of Informal Settlements. (November 2022) - Okem, Andrew Emmanuel; Makanishe, Timothee Bisimwa; Myeni, Sithembiso Lindelihle; Roberts, Debra Cynthia; Zungu, Sinethemba
The recent experiences and impact of the COVID-19 pandemic provide a valuable lens for understanding the vulnerabilities of informal settlements and how they are positioned to respond to other large-scale hazards. This article explores the body of knowledge on the pandemic in the context of informal settlements, guided by the scoping review strategy. Our findings reveal that COVID-19 has impacted informal settlements in several ways, including increasing loss of income, food insecurity, increased gender inequality, gender-based violence and forced evictions. While there have been numerous responses to the crisis, several pre-existing factors in informal settlements impeded their implementation. We note that lessons from the pandemic provide an important opportunity to address pre-existing vulnerabilities in informal settlements to make them more resilient to both health and environmental shocks.